(Invited) Investigations into the Formation of Germanene Using Electrochemical Atomic Layer Deposition (E-ALD). (13th April 2015) - Ledina, Maria; Liang, Xuehai; Kim, Youn-Geun; Jung, Jin; Perdue, Brian; Tsang, Chu; Soriaga, Manuel; Stickney, John Lewellen
Abstract : This paper will discuss possible formation of germanene electrochemically. Germanene should be a single layer allotrope of Ge. The techniques of in-situ electrochemical STM (EC-STM), voltammetry, coulometry, and micro-Raman have been used to investigate the electrochemical formation of germanene. Studies on Au(111) show that the initial deposition of Ge is kinetically slow and somewhat unstable, whereas the self-limited layer of Ge is stable and shows atomic distances of about 0.44 nm ± 0.02 nm. Micro-Raman was performed on Ge nanofilms, but only displayed a shift near 290 cm -1 in one area. Given the STM results, it appears that the coherence of the germanene domains will need to be increased in order to more consistently produce the Raman signal. The data presented suggest that germanene has been formed electrochemically, although only as a minority species.